(untitled) (Research, Society and Development, 2022)
Family-based agriculture is essential for the economic and social development of society. Cooperatives are organizations that act directly to promote this development process, whether local, regional or national. This study aims to analyze the contribution of cooperatives to the sustainability of family-based agriculture. For this purpose, a systematic review research was carried out, using the Web Of Science database. Fourteen scientific articles compose this review. Cooperation can be seen as an effective way to organize sustainable rural development in a structurally way, and family-based agriculture is the main actor in this process. Thus, cooperatives contribute as institutions of strategic actions in the survival of family-based agriculture, organizing, mobilizing and expanding possibilities and opportunities, prioritizing strategies aimed at rural family development and sustainability. Results permeate between four main topics in the analyzed articles, namely: farmers’ perception, cooperative practices, quality of life and management and satisfaction’s degree. It was also possible to perceive essential issues in the context of the insertion of the family farmer to the cooperative, generating more income, stability, security and prosperity on their properties, with the cooperative being seen as a way to promote the contribution in the boost of processes, social organization, management and economic information, as well as sustainable development.